Production of Ethnographic-Short Films on Karo Traditional Arts as Promotion and Dissemination of Local Wisdom Knowledge in Lingga Village, Simpang Empat District, Karo Regency - Arifninetrirosa; Rithaony; Sumarno, Edi (Talenta Publisher, 2023)
This Community Partnership Service Program aims to encourage a marketing strategy for Lingga village tourism through digital channels. Lingga Village has traditional Karo art activities which are still maintained today. The Nggara Simbelin Studio is an art studio that still maintains this traditional heritage. This activity aims to disseminate knowledge and practice of traditional Karo arts to the younger generation. The specific target of this activity is to strengthen the promotion of Lingga tourism village along with its traditional wealth in order to foreign and domestic tourists will again be attracted by comers from local or foreigners. This activity also documents the Karo traditional art of Lingga village so that it is easily accessible to the younger generation, especially in Lingga village, thereby assisting the process of inheriting local wisdom for long-term regeneration. The use of method in this activity is audio-visual ethnography, namely documentation with an ethnographic approach. This method will involve partners in the process of making ethnographic short films. From this experience of involvement, partners will understand more about the packaging process for traditional arts that they have as part of their promotion and dissemination strategy in the digital technology era. In the future, the existence of this ethnographic short film will help the people of Lingga village in terms of documenting one of the objects for promoting culture. In addition, this film will also be an additional learning tool for the process of dissemination and inheritance of the wealth of traditional Karo arts.